2015
DOI: 10.1021/acs.joc.5b01604
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure and Photoinduced Intramolecular Hydrogen Bonding in 2-Pyrrolylmethylidene Cycloalkanones

Abstract: The structures of pyrrolylmethylidene derivatives of 2,3-dihydro-1H-inden-1-one (3), 3,4-dihydro-naphthalen-1(2H)-one (4), and cycloalkanones (5-7) were studied for the first time in the solid state and solution by NMR, IR, and UV spectroscopies supported by DFT quantum mechanical calculations. It was shown that all studied compounds except cycloheptanone derivative 7 both in crystal and in solution exist in the form of dimers where single E or E,E configuration with respect to the exocyclic C═C bond is stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…However, these frequencies appear coupled to the close ν C=C bond. The decreased ν C=O intensity in compound 3 compared to 1 , further support the notion that charge transfer is weakening the C=O bond, which leads to reduction in the band's intensity and a blue shift to lower energy with considerable mixing with ν C=C stretching …”
Section: Introductionsupporting
confidence: 66%
“…However, these frequencies appear coupled to the close ν C=C bond. The decreased ν C=O intensity in compound 3 compared to 1 , further support the notion that charge transfer is weakening the C=O bond, which leads to reduction in the band's intensity and a blue shift to lower energy with considerable mixing with ν C=C stretching …”
Section: Introductionsupporting
confidence: 66%
“…[22] However, hydrogen bonding is not the only factor determining the relative stability of the 3-Z,E and 3-E,E isomers. Although being more sterically strained, it is strongly stabilized by two intramolecular hydrogen bonds that are not destroyed even by such a strong base as DMSO, as follows from the fact that the Z,Z-isomer remains most stable irrespective of the presence of solvent either as a continuum or as discrete molecules.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] 2-Indanone-based dienones 2 have been used as building blocks for the synthesis of biologically active compounds. [22] It was shown that all studied compounds except cycloheptanone derivative (n = 3) both in crystal and in solution, exist in the form of dimers in which the E-or E,E-configuration with respect to the exocyclic C=C bond is stabilized by N-H···O=C intermolecular hydrogen bonds. Recently, we studied pyrrolylidene derivatives of 1-indanone and bis-pyrrolylidene derivatives of cycloalkanones (1, Ar = 2-pyrrolyl, n = 1-3).…”
Section: Introductionmentioning
confidence: 98%
“…the ability to isomerize under UV irradiation [9e11]. Recently, we have shown that pyrrolylidene 1-indanone and -1-tetralone, which under normal conditions exist as E-isomers, when irradiated, isomerize to the Z-isomers possessing intramolecular hydrogen bond [12].…”
Section: Introductionmentioning
confidence: 99%
“…The reaction was carried out under the conditions successfully used for the reaction of 1-H-pyrrol-2-carbaldehyde with 1-indanone, that is, by reflux in ethanol in the presence of potassium hydroxide [12]. However, instead of the desired product of condensation, the potassium salt of the starting indanone 3-K was isolated.…”
Section: Introductionmentioning
confidence: 99%